2007
DOI: 10.1590/s0004-28032007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum concetrations of type III procollagen, hyluronic acid and histopathological findings in the liver of HCV-positive blood donors

Abstract: -Background -Serologic markers have been proposed for monitoring hepatic fibrosis in chronic liver disease. Among fibrosis markers, type III procollagen (PIIIP) and hyaluronic acid have been studied in these patients. Aim -To evaluate the association between these serum markers with histological findings. Methods -A prospective cross-sectional study was carried out with HCV-positive blood donors. The studied population included men and women whose age ranged from 18 to 60 years, with elevated liver function te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thus, circulating levels of PIIINP can be a biomarker of hepatic fibrogenesis [27,28]. In some observational studies, plasma PIIINP levels have been shown to be strongly associated with liver fibrosis in patients with chronic liver disease [29][30][31][32]. The best predictive value was reported, with an AUROC = 0.87 distinguishing fibrosis and cirrhosis from normal liver or steatosis in 45 cases with alcoholic liver disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, circulating levels of PIIINP can be a biomarker of hepatic fibrogenesis [27,28]. In some observational studies, plasma PIIINP levels have been shown to be strongly associated with liver fibrosis in patients with chronic liver disease [29][30][31][32]. The best predictive value was reported, with an AUROC = 0.87 distinguishing fibrosis and cirrhosis from normal liver or steatosis in 45 cases with alcoholic liver disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…Continued serum measurements of AST, alanine aminotransferase (ALT) and γ-glutamyl transferase (GGT) have been used to monitor patients [10][11][12]. In addition to these markers, some ECM components, such as procollagen type III, laminin, and hyaluronic acid (HA), have been used as biomarkers to predict liver fibrosis [13][14][15]. In HCV patients, the increase in serum HA is associated with the development of hepatic fibrosis and disease progression [16].…”
Section: Introductionmentioning
confidence: 99%